Korupsi di PT Pertamina dalam Perspektif Pemikiran Politik Islam: Antara Amanah, Keadilan, dan Pengawasan - Revana Revana; Vera Ayu Lestari; Meydilah Ayu Nafisah; Alfiki Istumetia Laila.R; Elza Putri; Dio Oktavio (International Forum of Researchers and Lecturers, 2025)
The corruption that occurred at PT Pertamina reflects the weak integrity of public officials and the inadequacy of internal oversight systems. The positive legal approach has proven ineffective in addressing corruption in practice. Therefore, this study departs from the need for an alternative approach based on Islamic political values such as trustworthiness (amanah), justice, and supervision in addressing corruption within state-owned enterprises (SOEs). This research employs a descriptive qualitative approach using a literature review method. Data were collected from academic journals, official reports by the Corruption Eradication Commission (KPK) and the Audit Board of Indonesia (BPK), as well as credible media sources. The data were analyzed by categorizing them according to the principles of trustworthiness, justice, and supervision, and then interpreted through the framework of Islamic political thought to deeply understand the root causes of corruption. Corruption in PT Pertamina involves power protection, budget manipulation, and procurement fraud. Violations of trust, injustice in resource distribution, and weak supervision indicate the absence of Islamic principles in corporate governance. Ethical and spiritual values have not yet been internalized within the bureaucratic system and organizational culture of SOEs. This study concludes that corruption in PT Pertamina is a result of the loss of trust, the breakdown of justice, and weak oversight. An Islamic political approach that emphasizes ethics and spiritual responsibility is highly relevant to be applied. These values can help form a just and transparent governance system and rebuild public trust in SOEs.